Elemental philosophy : earth, air, fire, and water as elemental ideas - Macauley, David (SUNY series in environmental philosophy and ethics., 2010)
"Bachelard called them "the hormones of the imagination." Hegel observed that, "through the four elements we have the elevation of sensuous ideas into thought." Earth, air, fire, and water are explored as both philosophical ideas and environmental issues associated with their classical and perennial conceptions. David Macauley embarks upon a wide-ranging discussion of their initial appearance in ancient Greek thought as mythic forces or scientific principles to their recent reemergence within contemporary continental philosophy as a means for understanding landscape and language, poetry and place, the body and the body politic. In so doing, he shows the importance of elemental thinking for comprehending and responding to ecological problems. In tracing changing views of the four elements through the history of ideas, Macauley generates a new vocabulary for and a fresh vision of the environment while engaging the elemental world directly with reflections on their various manifestations."--Jacket.